Pupils perception towards the implementation of environmental education across curriculum in Malaysia primary school - Abdullah, Nurul Hidayah Liew; Hamid, Hashima; Shafii, Haryati; Seow, Ta Wee; Ahmad, Jamilah (Institute of Physics Publishing, 2018)
Education is an important element in enhancing pupils' awareness on the environment. This is because education plays an important role in shaping and transforming society. In Malaysia, environmental education (EE) across curriculum has long been established. However, to date there is no specific assessment done to determine the successful implementation of these elements. Thus, the perception of pupils is needed to identify the needs of the implementer of the suitability and significance of EE across the curriculum on the pupils' environmental awareness. This study aims to identify the grade 6 pupils' perception toward the implementation of environmental education across curriculum in Malaysia primary school. The results showed that the pupils' perception of the environment was overall high and the location of the school does not significantly affect the pupils' perceptions of the environment. The majority of students defines the concept of the environment as objects. In addition, the percentage of pupils who give the concept of environmental rationally is also high. The perceptions of pupils on the need to protect the environment illustrate the majority agree on the benefits of future generations. The environmental concepts are presented somewhat rational and show the relationship between the environment and human beings. In conclusion, students' perceptions of the environment are positive and can determine it rationally and know the nature of natural disasters is a result of human action.